Communicative moves in forestry research introductions: implications for the design of learning materials - Renu Joseph; Lim, Jason Miin Hwa; Nor Arifah Mohd Nor (Elsevier, 2014)
This paper reports on a genre-based analysis of the rhetorical moves in research article introductions (RAIs) in Forestry, an established applied science discipline. Based on Swales’ (2004) revised CARS model, this study covers 20 RAs collected from four high impact Forestry journals. Our findings indicate that although Forestry RAIs largely conform to the revised CARS framework, prominent variations in step occurrences are noteworthy in comparison to those in other disciplines. The incidence of centrality claims in Forestry is significantly higher than those in some established disciplines. Research niches in Forestry are predominantly established using gap indications and positive justifications, thus showing (i) considerable similarity compared to those in Wildlife Behaviour, and (ii) notable difference compared to those in Civil Engineering. Hypothesis formulation also appears in half of the Forestry RAIs, thus exhibiting a significant distinction in comparison to those in Wildlife Behaviour and Civil Engineering. In terms of method-related summaries, Forestry resembles Civil Engineering rather than Wildlife Behaviour, given that two-thirds of Civil Engineering RAIs included such summative methodological statements while none of the writers in Wildlife Behaviour considered it necessary to incorporate this step in the beginning of a research paper. Based on the findings reported in this paper, we argue that rhetorical strategies actually constitute a crucial aspect in which different scientific disciplines can be distinguished and recognised. More importantly, varying degrees of emphasis need to be placed on different rhetorical steps while language instructors design teaching materials aimed at guiding learners in the writing of research introductions in courses on English for Research Purposes (ERP).